Islamic work ethics among employees of Islamic and conventional banks in Malaysia / Ahmad Saiful Azlin Puteh Salin … [et al.] - Ahmad Saiful Azlin Puteh Salin (Research Management Institute (RMI), 2012)
The current research intended to explore whether the religiosity play any critical role in influencing the work ethic of the employee. A lot of research that conducted in the area of the work ethic finds that there is a relationship between religiosity and work ethic. Zhu (2009) for example find that Confucian ethics are emphasis by Chine marketing managers while Parbooteah et al. (2009) finds that the cognitive, affective and the behavioural component of religion are negatively related to unethical practices. However, many of this research conducted are concentrated on the non-Islamic belief such as Confucius and Christianity while Islamic belief is widely missing in literature. Therefore, the current interested to examine the influence of Islamic work ethics among the employees of the bank. This study will review the fundamentals and the pillars of Islamic work ethic and investigates the empirical studies conducted on the banks in Malaysia. This research will extend the previous study by using a survey on the employees that works in conventional and Islamic banks. The sampling techniques is based on the systematic random sampling. In term of data analysis, descriptive analysis and inferential statistics will employed frequency, mean and other relevent statistical method to explain Islamic work ethic of the banks' employee generally, and to achieve the objectives of the study particularly. This study however only restricted to the full fledges Islamic and conventional banks and excluding the bank with a dual system. In addition, the sample selected only located in high density commercial areas in Malaysia, namely Klang Valley.